2011
DOI: 10.1021/jp203601w
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Centered Radicals in Iodine Chemical Oscillators

Abstract: The existence of free radicals in iodine-based oscillatory systems has been debated for some time. Recently, we have reported the presence of reactive oxygen species (ROS) in the iodide-peroxide system in acidic medium, which is common to all iodine--based oscillatory systems ( J. Phys. Chem. A 2011 , 115 , 2247--2249 ). In this work, the goal was to identify the ROS produced in this system using an EPR spin trap which can distinguish between hydroxyl (HO(•)) and hydroperoxyl (HOO(•)) radicals. The formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 33 publications
(39 reference statements)
2
31
0
1
Order By: Relevance
“…[17b] However,n oe fficient strategy has yet been reported to suppress nonproductive pathways (i.e., oxidative decomposition of oxidant) for I + /H 2 O 2 catalysis,a lthough the use of hydrogen peroxide is highly preferable because it is less expensive and more atom-economical than alkyl hydroperoxide. [22] Because the oxidative decomposition of hydrogen peroxide might involve radical intermediates, [20,23] and the present oxidative coupling reaction might proceed via an ionic mechanism, we found that the non-productive pathways of I + /H 2 O 2 catalysis could be suppressed by using ac atalytic amount of ar adical trapping agent such as a-phenyl-N-tertbutylnitrone (PBN) or 5-(diethoxyphosphoryl)-5-methyl-1pyrroline N-oxide (DEPMPO) ( Table 1, entries 4a nd 5, for further investigation of additives,s ee Table S1). Notably,i n comparison with the striking results using catalyst 3b shown in entry 4, unreacted 1b was almost recovered with the use of catalysts 3a, 3c and 3d under the same mild conditions ( Table 1, entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…[17b] However,n oe fficient strategy has yet been reported to suppress nonproductive pathways (i.e., oxidative decomposition of oxidant) for I + /H 2 O 2 catalysis,a lthough the use of hydrogen peroxide is highly preferable because it is less expensive and more atom-economical than alkyl hydroperoxide. [22] Because the oxidative decomposition of hydrogen peroxide might involve radical intermediates, [20,23] and the present oxidative coupling reaction might proceed via an ionic mechanism, we found that the non-productive pathways of I + /H 2 O 2 catalysis could be suppressed by using ac atalytic amount of ar adical trapping agent such as a-phenyl-N-tertbutylnitrone (PBN) or 5-(diethoxyphosphoryl)-5-methyl-1pyrroline N-oxide (DEPMPO) ( Table 1, entries 4a nd 5, for further investigation of additives,s ee Table S1). Notably,i n comparison with the striking results using catalyst 3b shown in entry 4, unreacted 1b was almost recovered with the use of catalysts 3a, 3c and 3d under the same mild conditions ( Table 1, entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…to give the a-azido products via S N 2' type addition of ammonium azide.O nt he other hand, based on the control experiments (Table S8), in situ generated I + species such as hypoiodite might be the catalytic active species for the present oxidative a-azidation reactions,a si no ur previous oxidative coupling reactions. [19,20,23] Based on these results, ap roposed catalytic mechanism is depicted in Scheme 6c, which consists of three main steps:oxidation of iodide to the hypoiodite active species,( decarboxylative) a-iodination of 1 or 5,and nucleophilic azidation of the corresponding a-iodo intermediate 9 or 10.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Smatra se da se reakcije koje inhibitorno utiču na oscilatornu dinamiku, uglavnom odigravaju sa prisutnim HOO• radikalima generisanim u BR reakciji. Ovo, naravno, treba uzeti sa rezervom jer je BR reakcija potencijalni generator i drugih radikalskih vrsta (IO2•, I•, HO•, MAH•, IMA•, poslednja dva su radikali nastali iz malonske kiseline (MA) i jodomalonske kiseline (IMA)), ali i neradikalskih vrsta kao što su HIO2, HIO, I2, I - [33][34][35][36][37][38]. Izazvane promene u oscilatornoj dinamici dodatkom aktivnog analita/aditiva, se uspešno koriste za određivanje koncentracije aktivnog analita, ali i njegove potencijalne antioksidativne/antiradikalske aktivnosti [30].…”
Section: Uvodunclassified